2004
DOI: 10.1183/09031936.04.00142903
|View full text |Cite
|
Sign up to set email alerts
|

HRCT lung abnormalities are not a surrogate for exercise limitation in bronchiectasis

Abstract: In paediatric bronchiectasis, there has been limited work on the relationship between disease severity as assessed by exercise limitation and high resolution computed tomography (HRCT).An observational study was performed on 36 children who completed a questionnaire, physical examination, spirometry and sputum analysis, followed by a low dose of radiation protocol chest computed tomography (CT) scan and cycle ergometry incremental exercise test. A modified Bhalla score was used to score the HRCT abnormalities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 47 publications
3
20
1
5
Order By: Relevance
“…A lot of studies have suggested that LCI has the advantage over FEV 1 to detect CF lung disease in earlier stages [21,36,38,[64][65][66][67][68]. A more sophisticated analysis of the SnIII has revealed the Scond and Sacin, as indices to detect the mechanisms of ventilation inhomogeneity and the location of the different ventilated lung units.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of studies have suggested that LCI has the advantage over FEV 1 to detect CF lung disease in earlier stages [21,36,38,[64][65][66][67][68]. A more sophisticated analysis of the SnIII has revealed the Scond and Sacin, as indices to detect the mechanisms of ventilation inhomogeneity and the location of the different ventilated lung units.…”
Section: Discussionmentioning
confidence: 99%
“…First, the data were collected at a single time point and no longitudinal findings could be used for comparison; therefore, the current authors were not able to comment on the progression of the radiological abnormalities and disease course. In addition, repeat CT would entail extra radiology, and recent evidence suggested CT abnormalities to be poor markers of exercise capacity and functional status [34]. Secondly, the patients were a selected group and there was a possibility of referral bias given the special interests of the two tertiary units: immunology (Great Ormond Street Hospital for Children), and PCD (Royal Brompton Hospital).…”
Section: Discussionmentioning
confidence: 99%
“…Exertional breathlessness is described in many case series 42 53 212 213 228. Children may also present with failure to thrive or malnutrition,53 212 213 although in the UK they are likely to be of normal weight and height 231. Less frequently described as presenting features are fever,228 chest pain228 and recurrent lower respiratory tract infection.…”
Section: Section 3: Clinical Assessment and Investigationsmentioning
confidence: 99%